Measuring efficiency, productivity and financial performance of Libyan manufacturing firms pre and post privatization / Mohamed Saad Mohamed Abokaresh - Mohamed Abokaresh, Mohamed Saad (Institute of Graduate Studies, UiTM, 2013)
This study examines the effect of privatization on technical efficiency, productivity and financial performance of 21 Libyan manufacturing firms from 2000 to 2008, and captures also the pre and post privatization effects of those measures, by applying the Frontier Data Envelopment Analysis (DEA) technique. Comparisons are also made meaningful by separating the firms into two ownership structures: state owned and fully privatized. As we are also assessing the pre and post privatization effects, the Wilcoxon Matched-Pairs Signed Rank Test is used to test for independence between-subjects designs. Technical efficiency scores of all manufacturing firms before and after privatization are computed using the input-oriented DEA model, proven to be suitable for determining technical efficiency. The findings from the analysis show that 42.9 per cent of the entire firms operate above average and 57.1 per cent operate below the average score. However, no firm has scored full efficiency (TE = 1.00). Even though the findings show an overall improvement in technical efficiency of 12.8 per cent, this is not consistent with the privatization theory. In evaluating the ownership types for pre and post privatization, the findings reveal that fully privatized firms are more efficient after privatization, implying better performance than state control firms. In terms of the Total Factor Productivity analysis, the findings show that the productivity of 16 (76.19 per cent) firms out of 21 firms decline after privatization…